ANALISIS PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA CAT CATYLAC DI KOTA AMBON - Sarifuddin Sarifuddin (Soso-Q : Jurnal Manajemen, 2021)
ABSTRAK This study aims to analyze the influence of brand image, brand trust on Catylac paintpurchasing decisions in Ambon City. This research is a descriptive study. By usinga questionnaire as a data collection tool as many as 58 respondents. Sampling usingpurposive sampling. The data analysis method used is Partial Least square usingSmartpls ver 3.0 includes validity and reliability tests, as well as hypothesis testingand model evaluation tests. -statistic exceeds the value> 1.96, then brand image isrelated and has no effect on purchasing decisions with a t-statistic value of 1.259because it has a T-statistic value of less than, <1.96 and brand trust is related andhas an effect on purchasing decisions with a t-statistic value of 6.062 because it hasa T-statistic value exceeding > 1.96. Keywords: Brand Image, Brand Trust, Purchase Decision